PENILAIAN PT. ELANG MAHKOTA TEKNOLOGI Tbk. PASCA AKUISISI PT. INDOSIAR MEDIA KARYA Tbk. TAHUN 2011 - , Ayon Suherman, S.E.; , Drs. Wakhid Slamet Ciptono,, MBA, MPM, Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this research is to estimate the fair market value of shares of PT Elang Mahkota Teknologi Tbk. in 2011 post-acquisition of PT Indosiar Media Karya Tbk. using two approaches, income approach discounted cash flow method (FCFF model) and market data approach (relative valuation). The data to be analyzed in this research was secondary data which collected from various sources. That data is consisted of consolitaded financial statement PT. Elang Mahkota Teknologi (audited) 2010-2011, annual report PT. Elang Mahkota Teknologi 2009-2011, EMTK stock price during the year 2011, composte stock price index for the year 2011, BI Rate, equity risk premium in 2011, and others supporting data. Analysis of the Discounted Cash Flow (FCFF models) is done by: projections of consolidated financial statements, the projected free cash flow to the company, determining the discount rate, the determination of terminal value, and determining the estimated value of the company. Analysis of relative valuation method begins by determining the comparison companies in similar lines of business subsequently select and assign a multiplier number (multiplies) that will be used to convert the book value of the relevant variables from PT Elang Mahkota Teknologi Tbk. be the estimated market value of equity. Multiplies used are: PER (Price to Earning Ratio), PBV (Price to Book Value) and Price to Sales Ratio. The results using the discounted cash flow estimates obtained by the intrinsic value of PT Elang Mahkota Teknologi Tbk. December 31, 2011 is Rp2.252, -, whereas the estimate based on the relative valuation of shares acquired shares of the intrinsic value per December 31, 2011 is Rp3.355, -. Reconciliation based on the average value of the two approaches produced the intrinsic value / fair market value of PT Elang Mahkota Teknologi Tbk. is Rp2.803 Based on sensitivity analysis, the fair market value is sensitive to changes in the discount rate, the rate of revenue growth and constant growth rate. The discount rate has a negative elasticity of the fair market value while the rate of revenue growth and constant growth has a positive elasticity.